Compound helicopter load alleviation in forward flight - Voskuijl, M.; Declerck, L. (My University, 2021)
The potential benefits of using redundant controls on a compound helicopter for manoeuvre load alleviation whilst optimizing handling qualities are investigated. The research is focused on forward flight lateral (roll) manoeuvres and hub loads. The main control effectors of interest are the ailerons and lateral cyclic pitch. A nonlinear simulation model of a compound version of the UH-60A Black Hawk helicopter is developed. Open-loop responses of the simulation model indicate that both the ailerons and lateral cyclic pitch can be used effectively for lateral control. However, these controls have a profoundly different effect on the hub loads. An analysis of the control strategy in trim, including other redundant controls such as compound thrust, reveals that the trim strategy has a major impact on steady state loads and the required power. Hence, there is an opportunity to optimize the control allocation strategy for load alleviation purposes. System identification techniques are used to obtain accurate linear models of the lateral dynamics for control law design. Roll attitude command, attitude hold (ACAH) control laws are developed for different gearing ratios between lateral cyclic pitch and aileron deflection. The control laws are optimized for handling qualities. The minimization of hub loads is the secondary objective. It is demonstrated that compared to conventional helicopter mode control or fixed-wing mode control, predicted handling qualities can be improved and hub loads can be reduced significantly (in the order of 30%-50%) for moderate to large amplitude manoeuvres if the gearing ratio between lateral cyclic pitch and aileron deflection is carefully selected.